(untitled) (Carte Romanze, 2023)
This article returns to the problematic issue of the location of the ms. Dublin, Trinity College Library, 269, which transmits texts apparently ascribable to the Cathar heresy and which is characterized by a scripta usually linked to the Alpine area. However, this initial study of the handwriting used by its three copyists allows to specify its location and to approximate it, at least partially, to the Waldensian manuscript production, identifying it as the oldest codex in which this peculiar scripta is used.